1977
DOI: 10.1073/pnas.74.3.801
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of tertiary structural change in hemoglobin.

Abstract: A reaction path is presented by which the effects of oxygen binding in hemoglobin are transmitted from a heme group to the surface of its subunit. Starting from the known deoxy geometry, it is shown by calculations with emirical energy functions and comparisons with available data Iow the change in heme geometry on ligation introduces a perturbation that leads to the tertiary structural alterations essential for cooperativity. It is found that there is little strain on the unliganded heme; instead, the reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(110 citation statements)
references
References 25 publications
3
107
0
Order By: Relevance
“…From fitting an improved set of experimental data on the pH dependence of oxygen binding, and allowing the salt bridges to have unequal strength, Karplus and coworkers found that K 5 K R , from which they concluded that there are additional constraints on ligand binding to T in addition to the salt bridges, which is presumably the strain in the allosteric core postulated by Gelin et al (22,53,54).…”
Section: The Generalized Szabo-karplus Model Of Lee and Karplusmentioning
confidence: 99%
See 2 more Smart Citations
“…From fitting an improved set of experimental data on the pH dependence of oxygen binding, and allowing the salt bridges to have unequal strength, Karplus and coworkers found that K 5 K R , from which they concluded that there are additional constraints on ligand binding to T in addition to the salt bridges, which is presumably the strain in the allosteric core postulated by Gelin et al (22,53,54).…”
Section: The Generalized Szabo-karplus Model Of Lee and Karplusmentioning
confidence: 99%
“…We associate the r and t conformations with the different conformations of the allosteric core described by Karplus and coworkers (53,54). Again, for clarity and simplicity, we only consider subunit conformations of the T quaternary structure at alkaline pH where all ionizable salt bridges are broken.…”
Section: Structural Interpretation Of the Tts Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural Basis for the Large Perturbation of the pK a of the Peptide Histidine-The experimentally determined pK a values of certain noncatalytic residues in naturally occurring proteins are shifted by as much as 2.5 units (46). Larger shifts in the pK a values often occur in functionally important residues, such as those at active sites where buried charged residues often participate in catalysis (47)(48)(49)(50)(51). For example, the pK a of active site Asp 26 in reduced thioredoxin is elevated by more than 5 units (52).…”
Section: Directionalities Of Hydrogen Bonds Involving Linear and Cyclmentioning
confidence: 99%
“…Gelin showed how the effect of undoming of the heme induced by the binding of oxygen was transmitted to the interface between the hemoglobin subunits. The analysis provided an essential element in the cooperative mechanism in its demonstration at an atomic level of detail how communication between the subunits occurred (35). Another application of pre-CHARMM was Dave Case's simulation of ligand escape after photodissociation from myoglobin (16); a study that was followed by the work of Ron Elber (25), which gave rise to the locally enhanced sampling (LES) and multiple copy simultaneous search (MCSS) methods.…”
Section: Origins Of the Charmm Programmentioning
confidence: 99%